Bile acid conjugation deficiency causes hypercholanemia, hyperphagia, islet dysfunction, and gut dysbiosis in mice. Issue 10 (22nd July 2022) - Alrehaili, Bandar D.; Lee, Mikang; Takahashi, Shogo; Novak, Robert; Rimal, Bipin; Boehme, Shannon; Trammell, Samuel A. J.; Grevengoed, Trisha J.; Kumar, Devendra; Alnouti, Yazen; Chiti, Katya; Wang, Xinwen; et al.
Abstract: Bile acid‐CoA: amino acid N‐acyltransferase (BAAT) catalyzes bile acid conjugation, the last step in bile acid synthesis. BAAT gene mutation in humans results in hypercholanemia, growth retardation, and fat‐soluble vitamin insufficiency. The current study investigated the physiological function of BAAT in bile acid and lipid metabolism using Baat −/− mice. The bile acid composition and hepatic gene expression were analyzed in 10‐week‐old Baat −/− mice. They were also challenged with a westernized diet (WD) for additional 15 weeks to assess the role of BAAT in bile acid, lipid, and glucose metabolism. Comprehensive lab animal monitoring system and cecal 16S ribosomal RNA gene sequencing were used to evaluate the energy metabolism and microbiome structure of the mice, respectively. In Baat −/− mice, hepatic bile acids were mostly unconjugated and their levels were significantly increased compared with wild‐type mice. Bile acid polyhydroxylation was markedly up‐regulated to detoxify unconjugated bile acid accumulated in Baat −/− mice. Although the level of serum marker of bile acid synthesis, 7α‐hydroxy‐4‐cholesten‐3‐one, was higher in Baat −/− mice, their bile acid pool size was smaller. When fed a WD, the Baat −/− mice showed a compromised body weight gain and impaired insulin secretion. The gut microbiome of Baat −/− mice showed a low level of sulfidogenic bacteria Bilophila . Conclusion : Mouse BAAT is the major taurine‐conjugating enzyme. Its deletion protected the animals from diet‐induced obesity, but caused glucose intolerance. The gut microbiome of the Baat −/− mice was altered to accommodate the unconjugated bile acid pool. Abstract : BaatKO mice exhibited almost complete absence of taurine conjugated bile acids in the liver. The mutant mice thrived on this hydrophobic bile acid condition via induction of BA hydroxylation mechanism with compromised body weight gaining.image